Two- way authentication system for ATM - Afaq Khan, Emad; Sumaira Muhmmad Hayat Khan, Dr (International Journal of Engineering and Technology, 2018)
This electronic document is research-based project that involves the use facial recognition in ATMs. This idea is not quite popular as in some points the facial recognition still lacks in credibility. This paper involves the research and the implementation phase of the facial recognition for ATM banking.Â Â